PEMIKIRAN USHUL AL-TAFSIR PERSPEKTIF MUSAID IBN SULAIMAN AL-THAYYAR - Maya, Rahendra; Sarbini, Muhammad; Alfarisi, Muhammad Fadilah; Bulloh, Muhammad Naji (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This research article aims to describe and analyze the fundamental thoughts of Musâ’id ibn Sulaimân Al-Thayyâr regarding Ushûl Al-Tafsîr in various related works, especially in five of his works which use the term and label Ushûl Al-Tafsîr. This research uses a qualitative research method with a descriptive literature study approach with data collection techniques through documentation studies using content analysis as a data analysis technique. Primary data sources are the five works of Musâ'id ibn Sulaimân Al-Thayyâr about Ushûl Al-Tafsîr, supported by secondary data source documents related to the theme of discussion of Ushûl Al-Tafsîr as well as the character of Musâ'id ibn Sulaimân Al-Thayyâr and his thoughts. The results of the research article show that Musâ'id ibn Sulaimân Al-Thayyâr is an academic lecturer who has high attention and is very consistent in studying Ushûl Al-Tafsîr as a scientific discipline in his work. Among his interesting thoughts about Ushûl Al-Tafsîr are those relating to the definition and essence of Ushûl Al-Tafsîr, the position of Ushûl Al-Tafsîr, the urgency and purpose of studying Ushûl Al-Tafsîr, and the objectivity of Ushûl Al-Tafsîr. It is hoped that Musâ'id ibn Sulaimân Al-Thayyâr's works regarding Ushûl Al-Tafsîr can be used as reading material and reference sources to overcome the scarcity of references to Ushûl Al-Tafsîr in Indonesia, including in the scientific-academic scope at Islamic religious universities